Nitrogen and phosphorus mineralization dynamics in human excreta-derived fertilizers - Bischak, Elena; Ghezzehei, Teamrat A.; Ryals, Rebecca (Frontiers in Agronomy, 2024)
Growing interest in human-excreta derived fertilizers requires more information on their agronomic relevance. In this study, we measured the nitrogen (N) and phosphorus (P) mineralization from fresh urine, stored urine, urine-enriched biochar prepared with either fresh or stored urine, and feces-derived compost application in a 90-day aerobic loam soil incubation. Soils were extracted for available N at days 0, 5, 10, 20, 30, 60, and 90, while soils were extracted for four biologically relevant P pools at days 0, 30, 60, and 90. We found that N in urine applied alone was immediately bioavailable, supplying nearly all the 200 kg-N ha-1 applied, while urine-enriched biochar supplied approximately half of the N applied. Feces-derived compost application led to a slow release of mineral N. Feces-derived compost application stimulated substantial native soil P mining, while urine-P was likely rapidly immobilized. These results are relevant to container-based sanitation and other source-separated sanitation endeavors, and researchers and producers interested in human excreta-derived fertilizers. Future research should explore, among other things, different urine-enriched biochar preparations and the co-application of urine-based fertilizers and feces-derived compost.